Soil protistology rebooted: 30 fundamental questions to start with. (August 2017) - Geisen, Stefan; Mitchell, Edward A.D.; Wilkinson, David M.; Adl, Sina; Bonkowski, Michael; Brown, Matthew W.; Fiore-Donno, Anna Maria; Heger, Thierry J.; Jassey, Vincent E.J.; Krashevska, Valentyna; Lahr, Daniel J.G.; Marcisz, Katarzyna; et al.
Abstract: Protists are the most diverse eukaryotes. These microbes are keystone organisms of soil ecosystems and regulate essential processes of soil fertility such as nutrient cycling and plant growth. Despite this, protists have received little scientific attention, especially compared to bacteria, fungi and nematodes in soil studies. Recent methodological advances, particularly in molecular biology techniques, have made the study of soil protists more accessible, and have created a resurgence of interest in soil protistology. This ongoing revolution now enables comprehensive investigations of the structure and functioning of soil protist communities, paving the way to a new era in soil biology. Instead of providing an exhaustive review, we provide a synthesis of research gaps that should be prioritized in future studies of soil protistology to guide this rapidly developing research area. Based on a synthesis of expert opinion we propose 30 key questions covering a broad range of topics including evolution, phylogenetics, functional ecology, macroecology, paleoecology, and methodologies. These questions highlight a diversity of topics that will establish soil protistology as a hub discipline connecting different fundamental and applied fields such as ecology, biogeography, evolution, plant-microbe interactions, agronomy, and conservation biology. We are convinced that soil protistology has the potential to be one of the most exciting frontiers in biology. Highlights: Protists are the most diverse eukaryotes in soils. They are key elements in the soil food web and are essential for plant functioning. Nevertheless, protists are highly understudied compared to other microorganisms. We here provide an overview of missing research gaps to guide future studies. This will allow bridging protistology to general microbiology and ecology in soils.